BARRIERS FACED BYTEACHERS DURING THE IMPLEMENTATION OF EFFECTIVE CURRICULUM IN NURSING EDUCATION AND TRAINING. (Contemporary Journal of Social Science Review, 2025)
Effective curriculum implementation is a cornerstone of quality nursing education. In Pakistan, particularly in under-resourced settings, nursing educators face significant barriers that hinder successful curriculum delivery. These challenges impact both the competence of future nurses and the quality of healthcare services. Objectives: This study aims to identify and analyze the barriers encountered by nursing faculty during the implementation of the nursing education and training curriculum. It further explores the impact of these obstacles on educational outcomes and proposes strategies to mitigate them. Methods: An analytical crosssectional study was conducted using astructured questionnaire administered to nursing faculty members from various public and private sector institutions in Sindh. Both online and face-to-face surveys were used to collect data. Descriptive and inferential statistical analysis was performed using SPSS (version 21). Results: Findings revealed multiple barriers including inadequate training opportunities, poor institutional support, insufficient resources, heavy workloads, limited access to teaching aids, and misaligned curriculum content. Faculty also reported lack of time, ineffective teaching methods, and gaps in professional development. These issues were further exacerbated by communication barriers and administrative constraints.Conclusion: Addressing these barriers is critical to improving the quality of nursing education. Targeted strategies such as faculty training, improved resource allocation, and administrative support are essential for effective curriculum implementation. Strengthening these areas can enhance teaching outcomes, support professional development, and ensure better healthcare delivery through well-trained nursing professionals.